Performance pay, training and labor mobility - Anne C. Gielen (Institute for the Study of Labor (IZA), 2007)
Market imperfections may cause firms and workers to under-invest in specific training. This paper shows that profit sharing may be a suitable instrument to enhance specific training investments, either by enhancing wage flexibility or by increasing the returns to training. As a result, profit sharing not only increases productivity by means of an effort effect, but also by increased training investments. Furthermore, the results suggest that older workers' employability can be improved if a profit-related remuneration is paid.
Keywords: 330; Erfolgsbeteiligung; Weiterbildung; Bildungsinvestition; Arbeitsproduktivität; Arbeitsmobilität; Großbritannien